A comparison of the erythrocyte glucose-6-phosphate dehydrogenase (G6PD) levels of mothers and their newborns - Hiçsönmez, Gönül; Özsoylu, Şinasi (The Turkish Journal of Pediatrics, 1968)
Erythrocyte G6PD activity was determined in 30 newborn babies and their mothers within 24 hours of parturition and com-